Adoption of Climate-Smart Cocoa practices in the adjust and cope climatic impact zones of Ghana - Dalaa, Mustapha Alasan; Deffor, Eric Worlanyo; Kofituo, Rich Kofi; Asare, Richard (International Institute of Tropical Agriculture, 2020)
Cocoa (Theobroma Caocao) remains an important crop to the Ghanaian economy, due its historical contribution to revenue, foreign exchange and the creation of direct and indirect jobs. The sector however continues to face production challenges such as aging cocoa trees, reduced soil fertility, pest and disease infestations and recently the effects of climate change. These threaten the productivity and sustainability of cocoa in Ghana. The introduction of Climate Smart Cocoa (CSC) practices for designated climate impact zones in Ghana thus offer significant avenue for improving productivity and livelihood of cocoa farmers (IITA, 2019).